Divergent relationship between brain structure and cognitive functioning in patients with prominent negative symptomatology. (30th January 2021) - Haatveit, Beathe; Mørch-Johnsen, Lynn; Alnæs, Dag; Engen, Magnus Johan; Lyngstad, Siv Hege; Færden, Ann; Agartz, Ingrid; Ueland, Torill; Melle, Ingrid
Highlights: Negative and cognitive symptoms are linked to abnormal brain structure. Schizophrenia is associated with abnormal brain structure of anterior cingulate cortex. Patients with prominent negative symptoms have poorer cognitive functioning. Better cognition is associated with larger volumes, surface area and thicker cortex. Patients with prominent negative symptoms have reverse structure-function relationship. Abstract: Investigating commonalities in underlying pathology of cognitive dysfunction and negative symptoms in schizophrenia is important, as both are core features of the disorder and linked to brain structure abnormalities. We aimed to explore the relationship between cognition, negative symptoms and brain structure in schizophrenia. A total of 225 patients with Schizophrenia spectrum disorder and 283 healthy controls from the Norwegian Thematically Organized Psychosis (TOP) cohort were included in this study. Patients were categorized into four patient subgroups based on severity of negative symptoms: no-negative- (NNS), threshold-negative- (TNS), moderate-negative- (MNS), and prominent-negative (PNS) subgroups. MRI measures of brain volume, mean cortical thickness and surface area from pre-selected brain regions were tested for relationships with general cognitive ability and negative symptom subgroups. Positive associations were found between brain volume, thickness, surface area and cognition in the dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC), fusiform gyrus (FG) and the left anterior cingulate cortex (ACC), but with no differences between subgroups. In the PNS subgroup, cognition was conversely negatively associated with brain volume in the left ACC. These results indicate that patients with prominent negative symptoms have different associations between cognition and brain structure in the left ACC, which may point to abnormal neurodevelopment.